2014 IEEE World Congress on Services 2014
DOI: 10.1109/services.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Student Blood Pressure by Support Vector Machine Using Facebook

Abstract: predicting human blood pressure (B.P) is an important aspect of primary emotion using Facebook has not yet been investigated. Primary emotions help a person to express her/his feelings, thoughts and understanding the importance of social connections using Facebook. Facebook contribute rich environment of primary emotion and famous social site having collection of information that concerned with primary emotions. The well-known machine learning approaches have known as novel methods for doing prediction using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The outcome showed that SVM can be prosperously applied for prediction of BP through primary emotions. On the contrary, validations signified that the error statistics of the SVM model marginally outperformed [ 32 ]. Barbe et al developed a logistic regression model to calibrate and correct an oscillometric monitor such that the device better corresponds to the Korotkoff method regardless of the health status of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome showed that SVM can be prosperously applied for prediction of BP through primary emotions. On the contrary, validations signified that the error statistics of the SVM model marginally outperformed [ 32 ]. Barbe et al developed a logistic regression model to calibrate and correct an oscillometric monitor such that the device better corresponds to the Korotkoff method regardless of the health status of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SVM and permanental classification both outperformed logistic regression. Khan et al (2014) proposed SVM for performing the prediction of BP with primary emotions using Facebook status. Current human BP and those belonging to up to six previous primary emotions were given as input variables.…”
Section: Introductionmentioning
confidence: 99%